(untitled) (Herald of the National Children’s Medical Center, 2024)
Abstract: With multiple and combined injuries, shock develops from 40 to 96%, and the mortality rate for polytrauma in children remains high at 16-22%. Materials and methods of research: In the aspect of clinical and anatomical investigation of the causes of mortality in children with polytrauma, we analyzed the medical histories of 284 patients with multiple and combined injuries treated at the Republican Scientific Center for Emergency Medical Care (RNCEMP) over the past 8 years (2015-2023. Results of the study: Emergency surgery in a child with polytrauma is an intervention with a high degree of operational risk. Carrying out active antishock therapy during and after surgery makes it possible to successfully perform operations on victims. The operation requires modern anesthesia with tracheal intubation and adequate pulmonary ventilationThe implementation of this set of measures in the last 4 years has led to a decrease in mortality in children with polytrauma to 8.9%. Conclusion: Among the injuries in children that led to death, transport trauma dominates. The main feature of traffic injuries is the high proportion of combined injuries. The nature and volume of care at the prehospital stage, the time and method of transportation, the timeliness and quality of medical measures in the clinic, i.e. the organization of the traumatological intensive care service determines the outcome of the injury.